Pyrolysis Characterization of Simulated Radioactive Solid Waste: Pyrolysis Behavior, Kinetics, and Product Distribution - Zhigang Wei; Lulu Dong; Wei Wang; Pan Ding; Wenqian Jiang; Chi Zuo; Lei Li; Minghui Tang (Energies)
The disposal of low-level and intermediate-level radioactive solid waste has aroused widespread concern. In this work, the pyrolysis characterizations of simulated radioactive solid waste, cotton gloves (CG), stain removal cloths (SRC), plastic bags (PB), shoe covers (SC), and ion exchange resins (IER), were analyzed using thermogravimetric analysis, Thermogravimetric–Fourier Transform Infrared Spectrometry–Mass Spectrometry (TG-FTIR-MS) and Pyrolysis-Gas Chromatography/Mass Spectrometry (Py-GC/MS). The main mass loss stages of CG, SRC, PB, SC, and IER were 240–500 °C, 210–500 °C, 400–550 °C, 180–610 °C, and 25–700 °C, respectively. The average activation energies calculated by three iso-conversional methods were 184.09–211.46 kJ/mol, 172.33–180.85 kJ/mol, 264.63–268.01 kJ/mol, 150.49–184.36 kJ/mol, and 150.72–151.66 kJ/mol, respectively. Pyrolysis of CG and SRC mainly produced CO2 and oxygenated compounds. SC generated large amounts of HCl during pyrolysis. Combined with rapid pyrolysis analysis, it was shown that CG and SRC mainly produced carbohydrates, aliphatic hydrocarbons, and aromatics. The pyrolysis products of SC mainly consisted of aliphatic hydrocarbons, aromatics, and acids. The pyrolysis products of PB were mainly olefins and alcohols. IER produced large amounts of aromatics during rapid pyrolysis. Specifically, the pyrolysis of IER generated some SO2. This work provides a theoretical basis and data support for the treatment of mixed combustible radioactive waste.